Fiscal Indicators - Gramlich, Edward M. 1939-2007 (OECD Publishing, 1990)
This paper is one of three in this Working Paper Series, along with those by Chouraqui et al. and Blanchard, in which the assessment of fiscal policy is reconsidered. It reviews the question of what type of budget indicators the OECD should compile. Instead of the cyclically-adjusted budget, it argues for compiling several indicators to indicate fiscal performance on several dimensions. One measure based entirely on identities can describe the debt-stabilisation gap, one can describe discretionary fiscal policy change, and one can describe the fiscal impact of the budget. Several sources of confusion can be cleared up with this multi-indicator approach: at the same time there will be the costs of explaining what indicator should be used for what purpose ...
Keywords: Economics